2013
DOI: 10.1002/eji.201343632
|View full text |Cite
|
Sign up to set email alerts
|

The immunopathogenesis of the HIV tuberculosis immune reconstitution inflammatory syndrome

Abstract: HIV-1 patients co-infected with some pathogens are at risk of developing the immune reconstitution inflammatory syndrome (IRIS) when initiating antiretroviral therapy (ART). IRIS is characterized by inflammation leading to the clinical worsening of a treated infection or the unmasking of a previously undiagnosed condition or infection. It is commonly associated with tuberculosis (TB), 8-43% of the HIV-TB co-infected patients prescribed with antitubercular treatment and ART develop TB-IRIS. Although IRIS hasbee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 67 publications
0
38
0
3
Order By: Relevance
“…This suppression leads to an expedient reconstitution of CD4 ϩ T cells, which then react to an accumulation of viable infections and/or residual microbial antigens acquired during immunosuppression. As a result, the host can experience a massive amount of inflammation in multiple organs, primarily the lungs and central nervous system (CNS) (30,31). This immunopathology is mediated through CD4 ϩ T cells (32), but it was previously shown that other cell types, such as CD8 cells, modulate the pathology by increasing the T reg :T effector ratio (33).…”
Section: Cd20mentioning
confidence: 99%
“…This suppression leads to an expedient reconstitution of CD4 ϩ T cells, which then react to an accumulation of viable infections and/or residual microbial antigens acquired during immunosuppression. As a result, the host can experience a massive amount of inflammation in multiple organs, primarily the lungs and central nervous system (CNS) (30,31). This immunopathology is mediated through CD4 ϩ T cells (32), but it was previously shown that other cell types, such as CD8 cells, modulate the pathology by increasing the T reg :T effector ratio (33).…”
Section: Cd20mentioning
confidence: 99%
“…26,27 However, TB-IRIS is not explained simply by a change in CD4 numbers, and innate cells are also implicated in the syndrome. 5,12 Neutrophils are increasingly recognized in TB pathology, 28-30 as we have described in TB-meningitis IRIS, 6 but they had not previously been studied in this detail.…”
Section: Ln Granulomas From Patients With Iris Show Significant Neutrmentioning
confidence: 94%
“…3 TB-IRIS has been associated with perturbations in both the adaptive and innate immune systems. 4,5 These include increased secretion of neutrophil-associated mediators such as S100A8/A9 and matrix metalloproteinases, [6][7][8] perforin and granzyme B by CD4 + T cells, 9 higher expression and imbalance of C1Q and C1-inhibitor (complement system), 10 activation of monocytes, 11 inflammasome and Toll-like receptor signaling 12,13 , as well as elevated chemokine and cytokine production [14][15][16] with a particular role for the IL-10 family. 17 Although rapid changes in CD4 + T-cell count have long been associated with all forms of IRIS, recent research has focused on these latter phenomena of inflammasome activation and release of soluble mediators from innate cells.…”
Section: Introductionmentioning
confidence: 99%
“…On estime que jusqu'à un tiers de la population mondiale est infectée de façon latente par Mtb, et que 5 à 10 % des personnes infectées évoluent vers une tuberculose active [2]. La co-infection par le VIH augmente considérablement la probabilité de réactivation et la sévérité de la tuberculose.…”
Section: Tuberculose Et Vih : Une Association Particulièrement Dangerunclassified